ACUTE PAIN NURSING CARE IN PATIENT WITH HEPATITIS B: A CASE STUDY - Okviasanti, Fanni; Anggraini, Dia Ayu; Purnomo, Aris Cahyo (Journal of Vocational Nursing, 2021)
Introduction: Severe pain in the upper right abdomen was commonly found in hepatitis B patients. Hepatitis B patients who experience pain take longer in the process of healing the disease than those who do not. Acute pain nursing care in hepatitis B patients is still unknown. This study aimed to describe acute pain nursing care in patients with hepatitis B. Methods: This study used a case study design. Data collection from assessment to nursing evaluation was carried out in the internal ward of a governmental hospital in Lamongan on November 2019. The hepatitis B patient was observed or treated for at least three days. Data collection techniques used interviews, observation, and documentation. Data analysis was performed using narrative analysis. Results: Assessment of Mr. A with the main complaint felt by the patient was a pain in the upper right abdomen. The nursing diagnosis in Mr. A's case was found to be an actual diagnosis with priority being acute pain relate to physiological injury agents (D.0077). Nursing interventions at Mr. A were arranged based on priority diagnosis with acute pain using pharmacological techniques and non-pharmacological techniques, and antibiotics. Conclusion: The nursing problem of Mr. A was resolved after 72 hours of nursing intervention. The patient displayed a decreased level of pain with a pain scale of 2, decreased restlessness, no grimace, no protective attitude, and absence of insomnia.